Determinan Akuntabilitas, Profesionalisme dan Independensi terhadap Kualitas Audit - Sri Anjarwati; Ayub Anjashara (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This study aims to examine the influence of accountability, professionalism and independence of auditors on the quality of audits in public accounting firms in the West Jakarta area. The population used by public accounting firms in the West Jakarta Region. The research uses a type of quantitative research, where the research uses variables, populations, samples, and data analysis tests. The sample in the study was 100 people, sampling by calculating the number of indicators based on the structural equation model. Sample selection technique using convenience sampling. Data analysis using the Smart PLS analysis tool. The results of the study show that professionalism and independence have a significant effect on audit quality, while accountability does not have a significant effect on audit quality. The results provide a synthesis that the better the professionalism and independence that the Auditor has, the better the quality of the audit produced. If the auditor has professionalism in carrying out his duties, he or she can be arbitrary and carried out with responsibility. An auditor who has an independent attitude in carrying out audit duties, cannot be influenced by several individuals who are interested in making quality audit reports. In addition, the Auditor has a strong stance and does not attach importance to his own interests.